Antiwear performance of ionic liquid+graphene dispersions with anomalous viscosity-temperature behavior. (June 2018) - Pamies, R.; Avilés, M.D.; Arias-Pardilla, J.; Espinosa, T.; Carrión, F.J.; Sanes, J.; Bermúdez, M.D.
Abstract: New dispersions of few-layers graphene (G) in 1-ethyl-3-methylimidazolium ([EMIM]) ionic liquids (ILs) with dicyanamide ([DCA]) or bis(trifluoromethylsulfonyl)imide ([TFSI]) anions have been obtained by mechanical mixing and sonication. IL+0.5 wt% G dispersions show constant viscosity values from 357K (for IL = [EMIM][DCA]) or from 385K (for IL = [EMIM][TFSI]) to 393K. IL + G dispersions with G > 0.5 wt% show linear viscosity increases with increasing temperature, from 306K (for [EMIM][DCA]+1 wt%G) and from 330K to 393K (for [EMIM][TFSI]+0.75 wt%G and [EMIM][TFSI]+1 wt%G). Addition of graphene improves the poor wear reducing performance of [EMIM][DCA], and prevents surface damage on steel when added to [EMIM][TFSI]. Graphene increases the load-carrying ability of ILs, forms a surface layer on the sliding path and retains wear debris, preventing the formation of large abrasive particles. Graphical abstract: Image 1 Highlights: Graphene prevents wear by a surface layer and inhibits large wear debris. Unprecedented rheology for ionic liquid + graphene nanolubricants is described. A critical 0.5 wt% graphene concentration for non-Newtonian efficient lubrication.